Sleep-related movement disorders in a population of patients with epilepsy: prevalence and impact of restless legs syndrome and sleep bruxism - Khachatryan, Samson G. (J Clin Sleep Med, 2020)
STUDY OBJECTIVES: Sleep disorders are frequent co-occurrences in patients with epilepsy (PWE), but sleep-disordered breathing and insomnia are better studied than others. Our aim was to study sleep-related movement disorders in epilepsy. METHODS: We interviewed 175 PWE (age range 18–71 years, mean 35.4 years, 47.4% female) and 130 controls (age range 18–72 years, mean 33.6 years, 47.7% females). Restless legs syndrome (RLS) and sleep bruxism (SB) were diagnosed by International RLS Study Group’s diagnostic criteria and International Classification of Sleep Disorders, Third Edition criteria respectively. We also used Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS) and Berlin Questionnaire (BQ). RESULTS: Our findings suggest that RLS and SB are encountered more frequently in PWE than controls: 20.6% versus 6.1% for RLS, and 23.7% versus 5.4% for SB (P < .05). Insomnia was more prevalent in epilepsy (46.2% versus 24.6%, P < .05) while poor sleep hygiene occurred more frequently in controls (28.3% versus 53.8%), (P < .05). PWE had poorer sleep by PSQI 61.7% versus 41.5% (P < .05). Sleepiness (38.7% versus 39.2%) and snoring (42.8% versus 40.8%) were equally distributed in both groups, also ESS and BQ not showing significant differences (P > .05). CONCLUSIONS: Our study demonstrates that sleep disorders comprise important part of epilepsy comorbidity. We demonstrated that unselected PWE had higher prevalence of RLS. For the first time we show higher prevalence of sleep bruxism in epilepsy population. Also complaints of insomnia are seen more in PWE, while snoring and poor sleep hygiene not. CITATION: Khachatryan SG, Ghahramanyan L, Tavadyan Z, Yeghiazaryan N, Attarian HP. Sleep-related movement disorders in a population of patients with epilepsy: prevalence and impact of restless legs syndrome and sleep bruxism. J Clin Sleep Med. 2020;16(3):409–414.